Implementasi Penilaian Autentik: Model Perangkat Pembelajaran dan Penilaian Matematika Dengan Pendekatan CTL Berbasis Budaya Islam - Syukrul Hamdi; Seni Ermawati (Educatio, 2018)
This study aims at implementing authentic assessments in mathematics learning in the classroom by developing mathematical learning and assessment tools with Islamic culture based Contextual Teaching and Learning approach that meet valid, practical, and effective requirements. The research procedure adopted the 4-D Development model, those are Defining, Planning, Developing and distributing stages. The instrument used to assist the research process consisted of (1) device validation sheet, (2) practicality questionnaire from the teacher, (3) student response questionnaire, (4) Instrument of student motivation and learning outcomes. The validity quality of learning devices meets valid criteria based on the average score of the syllabus which reaches 4.18, lesson plan 4.18, textbook 4.28, and the instrument meets the valid index based on the aikens formula. The practicality quality of learning devices meets practical criteria based on the assessment of practicality of the teacher in which the average score reaches 4.75, and the response questionnaire assessment of students is 493. Based on the result of Manova test, it can be concluded that the use of Mathematics learning and assessment model with Islamic culture based Contextual Teaching and Learning approaches is effective in terms of learning outcomes and student motivation.